2000
DOI: 10.1002/(sici)1097-0215(20000601)86:5<644::aid-ijc7>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

ERbB-2 expression is rate-limiting for epidermal growth factor-mediated stimulation of ovarian cancer cell proliferation

Abstract: Over‐expression of the ErbB‐2 proto‐oncogene frequently coincides with an aggressive clinical course of certain human adenocarcinomas. The ErbB‐2 receptor is a member of the ErbB family of growth factor receptors, and within this complex signaling network, ErbB‐2‐containing heterodimers are preferentially formed. To assess whether ErbB‐2 is a critical component in epidermal growth factor (EGF)–mediated stimulation of tumor cell proliferation, we used as a model SK‐OV‐3 ovarian cancer cells, which over‐express … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
(42 reference statements)
1
23
0
1
Order By: Relevance
“…Furthermore, it has been reported that EGFR-HER-2 heterodimers are rate-limiting in the EGF-mediated proliferation of tumour cells (Hsieh et al, 2000). These results suggested that EGFR and HER-2 may interact with each other and lead to effective antitumour activity.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it has been reported that EGFR-HER-2 heterodimers are rate-limiting in the EGF-mediated proliferation of tumour cells (Hsieh et al, 2000). These results suggested that EGFR and HER-2 may interact with each other and lead to effective antitumour activity.…”
Section: Discussionmentioning
confidence: 96%
“…Given that SK-OV-3 ovarian cancer cells are characterized by HER2 overexpression (Hsieh et al 2000) determining their fast, hormone-independent growth, we also examined HER2 transcript levels subject to ICB-1 knockdown. After analysis of HER2 expression by real-time RT-PCR, we observed a slight, but significant decrease of HER2 mRNA levels in SK-OV/icbKD cells by about 25% (Fig.…”
Section: Knockdown Of Icb-1 Gene In Mcf-7 Breast Cancer and Sk-ov-3 Omentioning
confidence: 87%
“…Yu et al (47) injected SKOV3 cells into immunodeficient mice, isolated a secondary cell line that expressed 2-fold greater levels of ErbB-2 than the parental SKOV3, and correlated this increased ErbB-2 expression with increased malignancy. Furthermore, Hsieh et al (48) created SKOV3 analogues with a range of reduced ErbB-2 expression and correlated increased ErbB-2 expression with an increase in EGFmediated proliferation. The model system described here also defines an SKOV3-derived cell line with increased ErbB-2 expression that correlates with the introduction and stimulation of LHR.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of ErbB-2 has been shown to increase proliferation, invasion, and migration in several human cancers (26,60), and studies in SKOV3 cells document a correlation between increased ErbB-2 protein expression and increased proliferation (47,48). However, in our SKOV3-based model system coexpressing LHR and ErbB-2, the LH-induced upregulation of ErbB-2 was insufficient in overcoming the negative effects of LHR on invasion, proliferation, or woundinduced migration and did not correlate with a more aggressive phenotype.…”
Section: Discussionmentioning
confidence: 99%